Product Traceability in Ceramic Industry 4.0: A Design Approach and Cloud-Based MES Prototype - Barata, João (2018)
We propose a customer-focused approach to design product traceability for Industry 4.0. Our design-science research includes a review of traceability technologies and participative enterprise modeling in the ceramic industry. We find benefits in com-bining Business Process Modeling Notation and Goal-oriented Requirements Lan-guage representations to (1) promote reflection by experts with different back-grounds, (2) reach consensus with a solution that addresses the goals of multiple stakeholders, and (3) ensure that customers’ needs are a priority in traceability de-sign. The resulting model combines technologies in different stages of the product lifecycle and is implemented in a cloud-based MES (Manufacturing Execution Sys-tem) prototype. Depending on each stage and strategic intention, the identification code can be embedded in the product, transport, or package. Our contribution can assist managers in the creation of cloud-based MES to support traceability integra-tion at (1) technological, (2) vertical, and (3) horizontal levels that are required in the fourth industrial revolution.